A new breast screening programme–an audit of the first year. Issue 783 (January 1991) - Kirby, R. M.; Williams, M.; Hopper, G.; Skinner, M. D.; French, C.; Suarez, V.; Summerly, M. E.; Gray, J. G.
Abstract : The experience of a new breast screening unit is reported. In the first 12 months there was a 72.1% response rate with 9890 women being screened. After the initial screen 598 (5.8%) were referred to the Assessment clinic. Following repeated mammography and clinical examination 166 patients were referred for a surgical opinion; 105 (1.06% of the total screened) were considered to be possibly malignant; 61 further patients with clinical and mammographically benign disease were kept under review by a single surgeon; 101 patients had excision biopsies; 28 of 32 palpable breast lumps and 36 of 69 non-palpable lesions proved to be malignant.